Kejadian Prediabetes pada Kelompok Usia Dewasa di Kota Jambi - Mohd. Syukri; Debbie Nomiko; Intan Permata Sari (Jurnal Keperawatan Silampari, 2022)
This study aims to analyze factors related to the incidence of prediabetes in the adult age group in the Putri Ayu Health Center Work Area, Jambi City, 2021. The research design used in this study was cross-sectional. The results showed that the incidence of prediabetes was 31.5%, and the factors related to the incidence of prediabetes were age (p-value = 0.006), physical activity (p-value = 0.001), and smoking habits (p-value = 0.000). In conclusion, preventing diabetes mellitus can be done by doing regular physical activity and avoiding smoking. Keywords: Physical Activity, Smoking, Prediabetes, Adult Age